Retrospective and prospective: insights from a decade of anesthesiology trends for perioperative health care - Xu, Wenjie; Suo, Zizheng; Qu, Yinyin; Zhou, Bowen; Zheng, Yuxiang; Ni, Cheng (Frontiers in Medicine, 2025)
This study analyzes research trends in anesthesiology over the past decade (2013–2023) by conducting a systematic keyword analysis of articles published in leading anesthesia journals, including Anesthesia, British Journal of Anesthesia, Anesthesiology, Journal of Clinical Anesthesia, and Anesthesia & Analgesia. Using the Bibliometrix software package (R version 3.5.6), we identified temporal patterns and journal-specific preferences in research themes. Early trends emphasized pain management, neuromuscular blockade, and perioperative physiology, while the COVID-19 pandemic shifted focus toward respiratory management and pandemic-related concerns. In recent years, research priorities have increasingly highlighted perioperative brain health, including postoperative cognitive dysfunction and delirium, alongside the integration of artificial intelligence to optimize perioperative care. These findings reflect the evolving landscape of anesthesiology, with a growing emphasis on mitigating postoperative complications and addressing the cognitive outcomes of surgical patients—issues of relevance to aging populations. By bridging gaps between research innovations and clinical application, this study underscores the importance of multidisciplinary collaboration to enhance patient outcomes and inform public health strategies in the perioperative setting.